Individualism, Collectivism and Management in China: Does Atlas Shrug in China?. Issue 3 (3rd July 2019) - Long, Zhang; Parnell, John A.; Dent, Eric B.
ABSTRACT: Rand's philosophy of objectivism has enjoyed a recent resurgence of interest in the United States, but little is known about how it is conceptualized in non-Western cultures and how it influences business practice. This paper investigates and supports the existence of a form of objectivism within the Chinese culture, drawing into question the notion that Chinese society is inherently collective. Results concerning an anticipated metaphysical dimension were inconclusive, suggesting that Chinese who embody epistemological, ethical, and political aspects of objectivism lack a corresponding and clear notion of causality, time, and identity.